2020
DOI: 10.1111/vop.12853
|View full text |Cite
|
Sign up to set email alerts
|

Presumed cancer‐associated retinopathy (CAR) mimicking Sudden Acquired Retinal Degeneration Syndrome (SARDS) in canines

Abstract: Objective To describe functional and structural features of presumed cancer‐associated retinopathy (CAR) mimicking sudden acquired retinal degeneration syndrome (SARDS) in dogs and describe treatment outcomes. Animals Subjects were 17 dogs from 8 eight US states and Canada diagnosed with SARDS or immune‐mediated retinitis (IMR) by 12 ophthalmologists. Nine eyes from seven deceased patients were used for microarray (MA), histology, or immunohistochemical (IHC) analysis. Procedures Dogs underwent complete ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
1
2
Order By: Relevance
“…In addition, a previous study demonstrated several focal retinal detachments on the OCTs of dogs with SARDS that were otherwise not identified during fundus examination. 3,8 No such findings were found in the OCT from Case 1 in our study. In the sighted OS, the band corresponding to the external limiting membrane (asterisk) was consistently present, while the ellipsoid zone and RPE photoreceptor interdigitations appeared to be merged as one band, except for in several areas where these bands were still discernable (arrows).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In addition, a previous study demonstrated several focal retinal detachments on the OCTs of dogs with SARDS that were otherwise not identified during fundus examination. 3,8 No such findings were found in the OCT from Case 1 in our study. In the sighted OS, the band corresponding to the external limiting membrane (asterisk) was consistently present, while the ellipsoid zone and RPE photoreceptor interdigitations appeared to be merged as one band, except for in several areas where these bands were still discernable (arrows).…”
Section: Discussioncontrasting
confidence: 62%
“…Therefore, it is interesting that despite having a barely discernible ellipsoid zone, the eye in this study still maintained vision and had a recordable ERG. In addition, a previous study demonstrated several focal retinal detachments on the OCTs of dogs with SARDS that were otherwise not identified during fundus examination 3,8 . No such findings were found in the OCT from Case 1 in our study.…”
Section: Discussioncontrasting
confidence: 50%
“…The condition resembles sudden acquired retinal degeneration syndrome (SARDS), though differences have been reported in the profile of retinal responses to different wavelengths of light (e.g., chromatic pupillometry). The condition is reported in people and suspected in dogs ( 85 ). As with SARDS a comprehensive workup including electroretinography and advanced imaging is recommended for a diagnosis that is largely reliant on exclusion.…”
Section: Neoplasticmentioning
confidence: 99%